Daya Dukung Masyarakat Terhadap Pengembangan Ekowisata Kawasan Tahura Pocut Meurah Intan Kabupaten Aceh Besar - Rizka Vianti; Abdullah Abdullah; Muhammad Rusdi (Biotik, 2018)
Tahura Pocut Meurah Intan in Aceh Besar is a nature conservation area that has various tourist attractions to be developed for ecotourism. This requires community support which is an important factor in ecotourism development. The purpose of this study was to find out the community's carrying capacity in the development of Tahura Pocut Meurah Intan ecotourism through 3 parameters, which are acceptance for visitors, participation in ecotourism development and participation in conservation. The study used descriptive method, while data was collected from questionnaires to villagers around the Tahura Pocut Meurah Intan, which are the Suka Damai Village, the Suka Mulia Village, and the Aceh Saree Village. The results showed that the community's carrying capacity for ecotourism development in the Tahura Pocut Meurah Intan in the SukaDamai Village was classified as supportive (70%) while the other two villages, the SukaMulia Village and the Aceh Saree Village were classified as very supportive (76.6%). It can be concluded that the community's carrying capacity in the development of the Tahura Pocut Meurah Intan as ecotourism area is very supportive, in terms of visitors' acceptance, community participation in ecotourism development, and community participation in conservation effort.